2006
DOI: 10.1590/s0100-204x2006000600013
|View full text |Cite
|
Sign up to set email alerts
|

Genes do eixo somatotrófico e características de crescimento numa população F2 de bovinos

Abstract: Resumo -O objetivo deste trabalho foi avaliar a associação dos polimorfismos dos genes bGH, IGF-1 e PIT-1 com características de peso e ganho de peso numa população F 2 de bovinos (Gir x Holandês), pela técnica de PCR-RFLP. As freqüências alélicas A e B, do gene PIT-1, e dos genótipos AA, AB e BB, nas populações parentais foram semelhantes entre si, mas diferentes das freqüências nas populações cruzadas F 1 e F 2 , para esse gene. Quanto ao gene bGH, os animais da raça Holandesa apresentaram freqüência de 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…The HinfI (-) allele was the less frequent in the two genetic groups (Table 1). The predominance of the HinfI (+) allele was also detected in different European cattle breeds (Moody et al, 1995;Sabour et al, 1996;Klauzinska et al, 2000;Oprzadek et al, 2003), in Gir and crossbred dairy cattle (Mattos, 2000), and in Gir × Holstein crosses (Silva et al, 2006).…”
Section: Allele Frequenciesmentioning
confidence: 85%
See 2 more Smart Citations
“…The HinfI (-) allele was the less frequent in the two genetic groups (Table 1). The predominance of the HinfI (+) allele was also detected in different European cattle breeds (Moody et al, 1995;Sabour et al, 1996;Klauzinska et al, 2000;Oprzadek et al, 2003), in Gir and crossbred dairy cattle (Mattos, 2000), and in Gir × Holstein crosses (Silva et al, 2006).…”
Section: Allele Frequenciesmentioning
confidence: 85%
“…PIT1 HinfI (-) allele was related to higher body weight at 7 months of age in double-muscled Belgian Blue bulls (Renaville et al, 1997) and higher weights at 60, 250, 365 days of age and on weight gain from born to 60 days of age in Gir × Holstein crosses (Silva et al, 2006). This polymorphism was associated with weaning weight in Nelore cattle (Conde et al, 2001).…”
Section: Allele Substitution Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…However, association between GH and weight at other ages, such as at weaning [36] and at 12 months of age [37], were observed for Canchim cattle. In an F2 population (derived from Holstein x Gyr crosses), Silva et al [38] found significant association (p \ 0.001) of GH with body weight at 365 days of age. Our analyses did not confirm an association between GH and weight at different ages (WB, WW, W12, and W18) but there is evidence that GH is responsible for 26 % (p = 0.03) and 7 % (p = 0.08) of the phenotypic variation of WFC and BW, respectively.…”
Section: Association Analysesmentioning
confidence: 99%
“…Zhang et al [46] found no significant association (p [ 0.05) of the POU1F1 gene (formerly named PIT1) with body weight traits measured at four months of age in Qinchuan breed and its crossings with Angus, Limousin, and Germany Yellow breeds. Other studies showed association of PIT1 with body weight in one line of Canchim cattle [21], in double-muscled Belgian Blue cattle [47], and in an F2 Holstein x Gyr population [38].…”
Section: Association Analysesmentioning
confidence: 99%